Reducing delay to endovascular reperfusion after relocating a thrombolysis unit - Laugesen, Nicolaj Grønbæk; Hansen, Klaus; Højgaard, Joan; Iversen, Helle Klingenberg; Truelsen, Thomas (Frontiers in Neurology, 2022)
Background and aims: Functional outcome following mechanical thrombectomy (MT) in patients with acute ischemic stroke and large vessel occlusion is time-dependent and worsens with increasing delay. Time to endovascular reperfusion is potentially modifiable with changes in organisational structure. We investigated the changes in time to reperfusion of relocating the intravenous thrombolysis (IVT) services from a non-MT center to a MT-capable center. Methods: We present an observational, consecutive, retrospective single center cohort study of 253 stroke patients treated with MT, 2017-2019. The observation period was divided into before and after relocation of IVT services in 2018, period 1 and period 2, respectively. The two hospitals were located 13 kilometres apart in an urban area and following the relocation, IVT was administered at the MT-capable center. Time metrics were registered and divided into two main intervals: ambulance departure from stroke onset location to imaging (ambulance-imaging) and imaging to reperfusion (imaging-reperfusion). The interval imaging-reperfusion included inter-hospital transfer to the MT-capable center in period 1. The association of the imaging-reperfusion duration and functional outcome at 90 days was analysed using ordinal logistic regression. Results: No significant change in ambulance-imaging was observed from a median of 27 minutes (interquartile range [IQR] 22-37) in period 1 to 30 minutes (IQR 23-40) in period 2, p=0.19, while median time of imaging-reperfusion decreased from 173 minutes (IQR 137-230) to 114 minutes (IQR 84-152), p<0.001. The largest absolute time reduction imaging to reperfusion seen was from imaging to arrival at the angio suite from 89 minutes (IQR 76-111) to 42 minutes (IQR 28-63), p<0.001, which included inter-hospital transfer in period 1. In multivariate analysis, every 10 minutes of increased delay from imaging to reperfusion was associated with poorer functional outcome with adjusted odds ratio 0.95 (95% CI:0.95-0.98), p<0.001. Conclusions: Relocation of IVT services to a MT-capable center was the main cause of reduced time to reperfusion for patients treated with MT and was implemented without affecting prehospital transportation time. These results suggest that patient outcome can be improved by optimising the organisation of IVT and MT services in urban areas.